Characteristics and Outcome of Headache in COVID-19 Patients in a Tertiary Care Centre of Bangladesh - Haque, Md Emdadul; Islam, Md Ashikul; Ahmed, Mohiuddin; Ahmed, Kazi Gias Uddin (Journal of Dhaka Medical College, 2025)
Background: Although the symptoms of coronavirus disease 2019 (COVID-19) are predominantly respiratory. Headache is one of the most frequent neurological symptoms. There is a wide variation in the prevalence of headaches, and little is known regarding the characteristics and outcomes of headaches in COVID-19 patients. So, this study aimed to determine the characteristics and headache outcomes among COVID-19 patients. Methods: This was a hospital-based prospective cohort study conducted in Dhaka Medical College Hospital from January 2021 to December 2021. Confirmed COVID-19 patients with Reverse Transcription Polymerase Chain Reaction (RT-PCR) were enrolled in the study. The severity of the headache was assessed by the Numerical Rating Scale (NRS, 0-10). All the patients with headaches were followed up by telephonic interviews in the 2nd week and at the end of the 4th week of the onset of the headache. For patients who experienced persistent headaches after 4th week, the impact of headaches on quality of life was assessed with the Headache Disability Index (HDI). Results: We included 362 patients in this study. The majority (52.5%) of the study population belonged to severe COVID-19 infection. Fever was the most common (63.81%) symptom among the study subjects. Headache was present in 19.06% of the patients. The mean (±SD) age of participants was 54(±14.7). Patients having headaches were younger 44.2±13.8 vs 56±13.8, p<0.05) than those have no headaches. Headache was more prevalent among the female (37[53.6%] vs 102[34.8%]). Tension-type headache (TTH) was the most common (60%) headache phenotype. The majority (68.12%) of the cases of headache occurred concomitantly with other COVID-19 symptoms. COVID-19-related headaches were, in most cases, bilateral, pressing, and of moderate intensity. Fever and pre-existing headaches were associated with significantly more frequency, duration, and intensity than COVID-19 headaches (p<0.05). Most patients (86.9%) recovered from headache within 4 weeks of onset. Median (IQR) recovery time was 10 (7.75) days. Nine patients (13.1%) did not recover from headaches in the 4th week of the survey. The Mean (±SD) HDI score was 24.4(±0.76) in patients who experienced headaches at the end of 4th week, which indicates mild disability. Conclusion: This study revealed that headache was present in about one-fifth of the hospitalized patients with COVID-19. Younger age and female gender were significantly associated with headaches. Most of the patients recovered within four weeks of the onset of headache. J Dhaka Med Coll. 2024; 33(1) : 18-26